Vegetation on geomorphic surfaces in the Monserrat Island in the Gulf of California - Ortiz-Ávila, Victor; Arnaud-Franco, Gustavo A.; Estrada-Castillón, Eduardo; Cavazos-Lozano, Eloy A.; Romero, Guillermo; Mellado, Miguel (Ecosistemas y Recursos Agropecuarios, 2020)
Knowledge about vegetation patterns along topographic gradients is crucial for conservation and management of arid islands. The objective of this study was to identify environmental, soil, and topography variables affecting plant distribution in Monserrat Island. A floristic and environmental survey was undertaken on this island (25° 41’ 00” N, 111° 03’ 00” W; 19.9 km2) in the Gulf of California, Mexico. Seven geoform zones were distinguished. The vegetation is predominantly a sarcocaule xerophilous scrub which develops mainly in ravines and bottoms of streams. One hundred fourteen species were recorded, of which 33 plants (28.9%) are endemic belonging to 92 genera and 38 families of vascular plants. The most abundant families were: Asteraceae, Euphorbiaceae, Fabaceae, Poaceae, and Cactaceae. The Bursera trees are more abundant in areas with little steep slopes (less than 25◦ ). On areas with steep slopes (greater than 45°), the development of vegetation is scarce. Northern exposure slopes had denser vegetation, with higher canopy cover values. Slope was far more reliably measure for describing vegetation distribution than altitude, although, the latter variable influences Olneya tesota. Euphorbia magdalenae was strongly associated with slope, and both Jouvea pilosa and Marina parryi was influenced by soil characteristics. Jatropha cuneata was found in almost all geoforms. It was concluded that Monserrat Island possesses a distinctive mix of xeric species making this island unique due to the high presence of endemic plants.